Eliciting real cravings with virtual food: Using immersive technologies to explore the effects of food stimuli in virtual reality - Harris, Nikita Mae; Lindeman, Robert W.; Bah, Clara Shui Fern; Gerhard, Daniel; Hoermann, Simon (Frontiers in Psychology, 2023)
In this paper, we explore the current technical possibilities of eating in virtual reality (VR) and show how this could be used to influence eating behaviors. Cue-based exposure therapy is a well-known method used to treat eating disorders. There are several benefits to using VR in combination with cue-based therapy. However, before VR-based cue-exposure can be used for therapeutic purposes, the ability of the VR environment to elicit craving responses in participants must be assessed. This was the objective of the first part of the study, where we assessed whether our VR environment elicited food craving responses in participants. Results showed that our VR environment elicited food craving responses: Salivation Magnitude, Food Craving State and Urge to Eat was significantly different from the neutral baseline. In addition, results showed that food cravings measured through the salivation magnitude in response to the virtual condition were not significantly different from the real condition, thus showing that VR had a comparable effect on producing food cravings. The second part of the study was conducted to determine whether the addition of olfactory and interaction cues in VR increased the development of food cravings. The results of this part showed that synthetic olfactory cues, paired with visual cues, provided a significant further increase in food cravings. Our results demonstrate that the use of food cues in VR can increase the development of food cravings and that it is possible to provide a simple yet convincing eating experience in VR. Inevitably, food interaction in VR is still under-explored territory and further research is needed to improve utility and application in disciplines related to food and eating.